Carboxyl-terminal mutants of the large tumor antigen of simian virus 40: a role for the early protein late in the lytic cycle. - Khalili, K (1988)
Simian virus 40 (SV40) mutants dl1066 and dl1140 contain deletions within the region encoding the carboxyl terminus of the large tumor (T) antigen. Although these mutations have little effect on the efficiency of viral DNA replication, they decrease the yield of infectious virus particles by 3-4 orders of magnitude [Pipas, J. (1985) J. Virol. 54, 569-575]. Here we show that the level of late RNA is lower by a factor of 5-15 in CV-1P monkey cells infected with these mutants compared to cells infected with wild-type SV40. Consistent with this decrease in RNA, synthesis of late viral structural proteins VP1 and VP3 decreases by a factor of 5-15. In contrast, the synthesis of SV40 agnoprotein decreases by a factor greater than 100. Intercistronic complementation of these mutants with pm1493 and dl121, two SV40 mutants that are defective in agnoprotein but encode wild-type T antigen, results in an increased synthesis of agnoprotein in the infected cells. These results suggest that the carboxyl-terminal portion of T antigen participates in the posttranscriptional regulation of agnoprotein.